Reproductive success of Fucus vesiculosus (Phaeophyceae) in the Baltic Sea - Serrão, Ester (2014)
Marine organisms colonizing brackish habitats such as the Baltic Sea must cope with the negative effects of low salinities on reproductive success because these may reduce gamete viability and/or increase polyspermy. Reproductive characteristics of the marine seaweed Fucus vesiculosus L. were studied in several brackish habitats, particularly in the northern Baltic Sea, to understand its ability to reproduce where few other marine species survive. Polyspermy and fertilization success were variable at the boundary of the continuous distribution of F. vesiculosus in the Baltic Sea, and polyspermy was high (10%–30%) when fertilization was successful. A strong female bias (80%–86%, ca. 5.5:1) was found at the northernmost limit of Baltic F. vesiculosus. Electrophysiological studies showed that many eggs have a high input resistance (519 ± 150 MΩ[mean ± SE, n = 14] at Drivan, 1995), which may be helpful in preventing polyspermy in this brackish habitat. The polyspermy block remains sodium-dependent in the northern Baltic. Sperm bound quickly to northern Baltic eggs in natural water, but fertilization was delayed compared to marine F. vesiculosus. A subset of northern Baltic eggs studied during an optimal reproductive period (7–11 July 1995) had a membrane potential (Em) of ca. −100 mV and an effective fertilization potential (FP) of ca. 2 min with a plateau of −25 mV, but repolarized too rapidly for the FP to be protective. Pronuclear migration and cell wall secretion occurred more slowly in Baltic than in marine zygotes. The reproductive success of theseboundary populations may be dependent upon windows of opportunity when there are favorable combinations of the levels of salinity, water motion, population density, and sex ratio. These factors and the short duration of the reproductive season in the northern Baltic Sea may result in reproductive failure in some years.